Solid Fermentation of Bacillus thuringiensis: Method Development - Thao, Nguyen Kim Nu; Linh, Do Thuy; Mai, Dinh Thi Ngoc; Hai, Pham The; Minh, Nguyen Hong (VNU Journal of Science: Natural Sciences and Technology, 2021)
Bacillus thuringiensis ( Bt ) is a significant bioinsecticidal agent that has been solely produced by liquid fermentation. With the increasing demand of bioinsecticides for organic agriculture, solid fermentation is preferred to enable low-cost and large-scale production of Bt. Therefore, in this study, we attempted to develop a solid state fermentation method to produce Bt by testing different solid substrates and also the effects of water percentage, fermentation time, temperature and seeding rate on the productions of biomass and parasporal crystal bodies (crystal proteins) of the Bt strain PAM33. Corn bran, rice bran and soybean meal are suitable to be utilized as substrates for biomass production. However, crystal proteins are only observed in solid fermentation using soybean meal as the substrate after 6 days of culture. The temperature range of 25-30°C and 10% seeding rate are the most suitable conditions for solid fermentation of strain PAM33 to obtain the bacterial density of approximate 10 9 CFU/g and the highest quantity of crystal proteins. This study shows that solid fermentation of Bt is feasible and effective to obtain bacterial biomass and crytal proteins by using cheap and available agricultural wastes. Thus, it can be a potential approach to produce the important Bt -based insecticide products for use in organic agriculture.